Letter: probable neuropsychiatric toxicity of polyethylene glycol: roles of media, internet and the caregivers—author reply. Issue 4 (22nd August 2019) - Misra, Sudipta; Hussain, Sunny Z.; Belkind‐Gerson, Jaime; Bhuiyan, Mohammad A. N.; Hicks, Timothy
Abstract : Linked Content This article is linked to Hussain et al and Chittenden papers. To view these articles, visithttps://doi.org/10.1002/ygh2.336 andhttps://doi.org/10.1002/ygh2.360 .